Evolving Experience in The Management of Empyema Thoracis - Shrestha, K; Shah, S; Shrestha, S; Thulung, S; Karki, B; Pokhrel, D P (Kathmandu University Medical Journal, 2012)
Background Empyema thoracis a disease of significant morbidity and mortality, especially in the developing world. However, the optimal management of empyema thoracis remains controversial. Objective To analyse evolving experience in clinical presentation, management, outcome and factors contributing to adverse morbidity in empyema thoracis. Methods This is hospital based retrospective study of patients who were diagnosed with empyema thoracis in cardiothoracic and vascular surgery (CTVS) unit, Bir Hospital, Kathmandu, Nepal over a period of one year (July 2009 to June 2010). A total of forty-six adult cases were categorized into two treatment groups: (i) thoracotomy for decortication (ii) segmentectomy, lobectomy and redo-thoracotomy for pneumonectomy. The median duration of illness prior to hospital admission was compared. The presence of loculated pleural fluid determined the need for thoracotomy. Results Out of forty-six cases, twenty- nine (63.04%) who had early thoracotomy (<22 days) had prompt symptomatic recovery. Forteen out of seventeen (82.35%) of the patients who were initially treated with thoracocentesis or tube thoracostomy eventually needed thoracotomy. There was a positive shift in management towards early thoracotomy resulting in prompt symptomatic recovery. Significant complications were noted in eight patients who had delayed thoracotomy. Complications included recurrent empyema with lung abscess (n = 3), restrictive lung disease (n = 3), bronchopleural fistula (n = 1) and scoliosis (n=1). Conclusion Early thoracotomy and decortication was found to be an excellent surgical procedure with good functional results and high patient satisfaction rate. http://dx.doi.org/10.3126/kumj.v9i1.6253 Kathmandu Univ Med J 2011;9(1):5-7